Evaluasi Tentang Pemungutan Pajak Bumi Dan Bangunan Sebagai Pendapatan Pajak Daerah Di Kota Jambi - Muhrizal, Muhrizal; Iqbal, Johandri; Adinda, Pramesti Nurul (Journal of Applied Accounting And Business, 2024)
The influence of the evaluation of land and building tax collection carried out by the government in carrying out its rights and obligations as a fiscus, especially in the regional sector of Jambi City entitled "Evaluation of Land and Building Tax Collection as Regional Tax Revenue in Jambi City (Case Study of the Agency Management of Regional Taxes and Levies)" at the Tax Accounting Department, Jambi Polytechnic. This research, which was supervised by Johandri Iqbal SE., M.S.Ak, and Pramesti Nurul Adinda, S.E, MM, used the descriptive qualitative research method. This study focuses on the evaluation system for collecting land and building tax at the Office of the Regional Tax and Levy Management Agency in Jambi City, with data on the realization target for PBB collection in Jambi City from 2018 to 2022. The results of the research show that Jambi City's land and building tax collection in 2018 and in 2019 there was quite a decrease, but from the 5 years presented, the calculations in 2020, 2021 and 2022 obtained results that increased and increased greatly